Education in Diabetes Mellitus for blood glucose self-monitoring: a quasi-experimental study - Marcelo Henrique Barbosa Baptista; Fernanda Cristina Dourado; Danielle dos Santos Gomides; Carla Regina de Souza Teixeira; Maria Cristina Foss de Freitas; Ana Emilia Pace
ABSTRACT Objective: to evaluate the contributions of an educational program for capillary blood glucose self-monitoring. Method: a quasi-experimental study performed in an outpatient unit of a tertiary health care service in a sample of 25 people with Type 2 Diabetes Mellitus, from July 2016 to December 2017, developed through interactive tools for care with capillary blood glucose self-monitoring. Results: among the items of capillary blood glucose self-monitoring that showed improvement after participation in the educational program, the most noteworthy are the "postprandial blood glucose values" (p=0.0039), "Interpretation of capillary blood glucose results with meals and medications" (p=0.0156), "recognition of the 'weakness' symptom for hyperglycemia" (p=0.0386) and "administration of medications correctly" for hyperglycemia prevention (p=0.0063). Conclusion: the study made it possible to recognize the main characteristics of blood glucose self-monitoring that may contribute to the care for the person with diabetes.